2008
DOI: 10.1029/2008gl034209
|View full text |Cite
|
Sign up to set email alerts
|

Association of Antarctic polar stratospheric cloud formation on tropospheric cloud systems

Abstract: [1] The formation of polar stratospheric clouds (PSCs) is critical to the development of polar ozone loss. However, the mechanisms of PSC formation remain poorly understood, which affects ozone loss models. Here, based on observations by the NASA A-train satellites, we show that 66% ± 16% and 52% ± 17% of PSCs over west and east Antarctica during the period June -October 2006 were associated with deep tropospheric cloud systems, with maximum depths exceeding 7 km. The development of such deep tropospheric clou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 22 publications
1
52
0
Order By: Relevance
“…Although PSCs are commonly observed over most of the Antarctic region in austral winter (June to September), the most favorable regions for PSCs are over the Antarctic Peninsula and ice sheets of the East Antarctic (Pitts et al, 2007;Wang et al, 2008). In contrast, PSCs appear sporadically in the Northern Hemisphere winter.…”
Section: Introductionmentioning
confidence: 96%
“…Although PSCs are commonly observed over most of the Antarctic region in austral winter (June to September), the most favorable regions for PSCs are over the Antarctic Peninsula and ice sheets of the East Antarctic (Pitts et al, 2007;Wang et al, 2008). In contrast, PSCs appear sporadically in the Northern Hemisphere winter.…”
Section: Introductionmentioning
confidence: 96%
“…Ice, water/liquid, and mixed-phase clouds are identified for up to 10 layers. The 2B-CLDCLASS-lidar collocates CALIOP L1 measurements to CPR footprints, then determines cloud vertical structures (Wang et al, 2008) and cloud phase. The microphysical property differences between water and ice particles, including size, location, falling speed, and number concentrations, result in large differences in their radiative properties, and in turn large differences in the CALIPSO lidar and CloudSat CPR signals.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies that used satellite observations (Palm et al, 2005;Wang et al, 2008;Adhikari et al, 2010) have reported that PSCs in the Antarctic are frequently observed simultaneously with upper-tropospheric clouds (UCs). Palm et al (2005) suggested that tropospheric disturbances may contribute to the formation of PSCs.…”
Section: Kohma and K Sato: Polar Stratospheric Clouds And Upper-tmentioning
confidence: 99%